Deflection of Positively Charged Heavy Particles by the Crystal Miscut Surface; Charged and Neutral Particles Channeling Phenomena. Channeling 2014 - Babaev A. A. Anton Anatoljevich (S6: Crystal Simultaion Routines for Particle Accelerators : Comparison and Benchmarkingwith Experimental Data / 129, 2014)
Заглавие с экрана